Severe ocular side effects of perhexilene maleate: case report. Issue 8 (August 1984) - Gibson, J M; Fielder, A R; Garner, A; Millac, P
Abstract : We report a case of perhexilene maleate (PEXID) toxicity in which the presenting feature was loss of vision secondary to chronic papilloedema. Vortex keratopathy similar to that seen in amiodarone keratopathy was present, and corneal and conjunctival biopsy findings are presented. To our knowledge this is the first case report of a keratopathy occurring in perhexilene toxicity. After withdrawal of the drug the papilloedema and keratopathy subsided, but some visual deficit remains. The properties of perhexilene maleate and other amphiphilic drugs are described, and the possible aetiology of vortex keratopathy is discussed.